Membawa Masa Lalu ke Masa Kini: Studi Fenomenologis Tentang Ruminasi Terhadap Pengalaman Masa Lalu dalam Mengikat Pola Perilaku Individu - Nani Riyani; Euis Nurhidayati (Journal of Society Counseling, 2026)
Rumination, defined as repetitive thinking about negative emotional experiences, plays a critical role in maintaining psychological distress and shaping individuals’ behavioral patterns. However, prior research has been predominantly quantitative, offering limited insight into the subjective lived experiences of rumination. This study aims to explore individuals' lived experiences of rumination related to past events and to examine its role in shaping recurring life patterns and its implications for personal potential development. A qualitative phenomenological design was employed, involving four purposively selected participants with experiences of rumination. Data were collected through in-depth interviews, participant observation, and field notes, and analyzed using Colaizzi’s phenomenological method. The findings revealed four major themes: rumination about past trauma, the formation of recurring life patterns, impacts on personal potential, and coping mechanisms. The results indicate that rumination functions as a linking mechanism between past experiences and present responses, forming a maladaptive psychological cycle that sustains negative emotions and constrains individual development. Furthermore, the coping strategies employed by participants were largely insufficient to disrupt this cycle. This study concludes that rumination is a complex phenomenon involving the interaction of cognitive, emotional, and experiential processes, highlighting the need for multidimensional interventions that integrate cognitive, emotional regulation, social, and spiritual components to effectively break recurring patterns and optimize individual potential.